Estrogen Concentration on Friesian Holstein Crossbred with Supplementation Feed Cassava Peel - Zulfarniansyah, Akhmad Baihaqi; Safitri, Erma (Jurnal Medik Veteriner, 2022)
The purpose of this study was to determine the ratio of estrogen concentrations given cassava peel feed supplementation. A total of 24 cows of Friesian Holstein, weighing 250-300 kg were divided into two groups and each group contains 12 replications. The first group is Friesian Holstein breeds with the condition that they are given elephant grass feed ad libitum and 25 kg of tofu dregs. The second group is Friesian Holstein breeds with the condition that they are fed ad libitum elephant grass, 25 kg of tofu dregs, and 25 kg of cassava peel. The milk samples were then taken to be tested for estrogen levels using the direct competitive ELISA. Analysis of estrogen concentration data was then carried out by normality test using Shapiro Wilk test then followed by the Paired T-test with a significance level of 5%. Based on the Paired T sample correlation test was 0.072 (p>0.05), which means that the feed gave the cassava peel and not the cassava peel was negatively associated. Based on the Paired T-test is 0.193 (p>0.05), which means there is no significant relationship between the 2 test groups. It can be concluded that there is no significant difference in the estrogen concentration of Friesian Holstein cattle fed with and without cassava peel supplementation.